Development of a Polymeric Nanoparticle for Gene Silencing in the Posterior Segment of the Eye - Monteiro, Amber (My University, 2024)
Age-related macular degeneration (AMD) is a retinal disease affecting over 200 million people that progresses to vision loss when left untreated. The neovascular form can be treated by bimonthly intravitreal injections of biologics that target vascular endothelial growth factor (VEGF) to inhibit dysregulated angiogenesis. Injection risks and logistics lower patient compliance, however even patients receiving optimal treatment can deteriorate. RNA interference (RNAi) via the delivery of small interfering RNA (siRNA) is under investigation as a therapeutic alternative. RNAi induces post-transcriptional gene silencing, providing more potent and longer-lasting effects. It has shown great therapeutic potential but is often limited by instability, reducing efficacy. In the current work, a cationic block co-polymer was developed and investigated as a delivery system for anti-VEGF siRNA to the posterior segment of the eye. This thesis details the synthesis, characterization, in vitro, and ex vivo testing of the polymer and the subsequent polyplexes formed between the polymer and an antisense oligonucleotide (ASO). pH-dependent polyplexes were formed which fully complexed the ASO at 1:1 and 10:1 ratios of polymer amine groups to ASO phosphate groups (N/P ratio). Although an increased N/P ratio is often found to cause cytotoxicity, neither formulation displayed a reduction in cell viability (p > 0.05). The polyplexes were under 150 nm in diameter, with a slightly negative zeta potential. In comparison to the naked ASO, the 10:1 polyplexes achieved superior transfection (p < 0.0001) into a human retinal pigment epithelial cell line (ARPE-19). After 24 hours, 0.6 μg of the ASO delivered by the 10:1 polyplexes displayed knockdown of the target protein (p < 0.05). Intravitreally administered polyplexes were well distributed throughout the vitreous humour, retina, and choroid within 4 hours of administration in an ex vivo porcine eye. These materials show potential for gene delivery in the treatment of AMD.
Keywords: polyplex; retina; gene delivery; age-related macular degeneration; copolymer; RNA interference